2019
DOI: 10.2478/s11686-019-00095-z
|View full text |Cite
|
Sign up to set email alerts
|

Multimethodological Approach to Gastrointestinal Microsporidiosis in HIV-Infected Patients

Abstract: Purpose Microsporidiosis is an opportunistic infection that produces chronic diarrhoea and cholangiopathy in patients with AIDS, mainly caused by two species of microsporidia, Enterocytozoon bieneusi and Encephalitozon intestinalis. The aim of this work was to develop an integral system for the diagnosis of microsporidiosis of the intestine and biliary tract in HIVinfected patients, comprising microscopic and molecular techniques. Methods The study population comprised 143 adult patients of both sexes with dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 97 publications
(102 reference statements)
0
4
1
Order By: Relevance
“…The prevalence of intestinal microsporidiosis in the present study is comparable to the pooled prevalence of 13.0% in Eastern Europe and Central Asia, 14.4% in Western and Central Europe and North America and 15.4% in sub-Saharan Africa [ 25 ]. Compared to the present study, prevalence rates of 11.3–16.6% among HIV/AIDS patients were reported from Mali, Venezuela, Addis Ababa of Ethiopia, Benin city of Nigeria, Chandigarh city of India and Burkina Faso (using microscopy), from Kerman city of Iran, Tunisia and Guangxi region of China (using PCR), Russia (using serological testing) and Argentina using TEM [ 16 , 17 , 30 – 38 ]. However, much lower prevalence rates of 0.8–8.5% were reported among HIV/AIDS patients from the United States of America, France, Kinshasa city of the Democratic Republic of the Congo (using PCR), Shiraz city of Iran, Bamenda city of Cameroon, Lucknow city of India (using PCR), Malaysia, the Abeokuta and Niger states of Nigeria and Hunan province of China [ 39 48 ].…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…The prevalence of intestinal microsporidiosis in the present study is comparable to the pooled prevalence of 13.0% in Eastern Europe and Central Asia, 14.4% in Western and Central Europe and North America and 15.4% in sub-Saharan Africa [ 25 ]. Compared to the present study, prevalence rates of 11.3–16.6% among HIV/AIDS patients were reported from Mali, Venezuela, Addis Ababa of Ethiopia, Benin city of Nigeria, Chandigarh city of India and Burkina Faso (using microscopy), from Kerman city of Iran, Tunisia and Guangxi region of China (using PCR), Russia (using serological testing) and Argentina using TEM [ 16 , 17 , 30 – 38 ]. However, much lower prevalence rates of 0.8–8.5% were reported among HIV/AIDS patients from the United States of America, France, Kinshasa city of the Democratic Republic of the Congo (using PCR), Shiraz city of Iran, Bamenda city of Cameroon, Lucknow city of India (using PCR), Malaysia, the Abeokuta and Niger states of Nigeria and Hunan province of China [ 39 48 ].…”
Section: Discussioncontrasting
confidence: 70%
“…Different laboratory techniques have been used to identify microsporidian spores in various clinical specimens, including light and fluorescence microscopy, transmission electron microscopy (TEM) as well as immunological and molecular techniques [ 16 ]. TEM is the gold standard technique to identify the specific species; however, it is time-consuming, expensive and cannot be performed on a large number of samples [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of rabbits in which encephalitozoonosis was diagnosed were simultaneously affected by other diseases such as myxomatosis, pneumonic pasteurellosis or skin abscesses, or were highly parasitized. As described in humans, it seems feasible that immunosuppressive conditions might have encouraged infection and the clinical picture [24,25]. In the cases of intestinal coccidiosis, the severity of the clinical and pathological findings made highly pathogenic species such as E. magna and E. intestinalis the most likely etiology.…”
Section: Discussionmentioning
confidence: 98%
“…Although intestinal microsporidiosis is prevalent in children residing in developing countries, scarce studies have been reported in Argentina ( 1 , 5 , 6 ). We present a case of E. bieneusi (genotype D) infection in a child who underwent unrelated allogeneic HSCT in Buenos Aires, Argentina.…”
mentioning
confidence: 99%